2013
DOI: 10.1088/0957-4484/24/37/375602
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic growth of NiO nanorods from Ni nanoparticles by rapid thermal oxidation

Abstract: NiO nanorods with extremely high crystallinity were grown by rapid thermal oxidation through exposure of Ni nanoparticles (NPs) heated above 400° C to oxygen. Oxidation proceeds by nucleation of a NiO island on a Ni NP that grows anisotropically to produce a NiO nanorod. This process differs completely from that under mild oxidation conditions, where the surface of the NPs is completely covered with an oxide film during the early stage of oxidation. The observed novel behaviour strongly suggests an interfacial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The Ni-O phase diagram shows that (below1 700 K), there exists only two phases, Ni and NiO (Kowalski and Spencer 1995). In the case of Koga et al, the oxidation is shown to take place not only at 400°C and P O 2 = 533 Pa but also at 900°C and 1.6 Pa (Koga and Hirasawa 2013). These numbers can be compared with the present work where 0.08 sccm results in P O 2 = 0.2 Pa, if an ideal gas mixture is assumed.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The Ni-O phase diagram shows that (below1 700 K), there exists only two phases, Ni and NiO (Kowalski and Spencer 1995). In the case of Koga et al, the oxidation is shown to take place not only at 400°C and P O 2 = 533 Pa but also at 900°C and 1.6 Pa (Koga and Hirasawa 2013). These numbers can be compared with the present work where 0.08 sccm results in P O 2 = 0.2 Pa, if an ideal gas mixture is assumed.…”
Section: Discussionmentioning
confidence: 95%
“…This has important consequences for the synthesis and structure evolution of nanoparticles of Ni and NiO in oxygen environments. This was described elegantly by Koga and Hirasawa (2013) in post-oxidation of spherical Ni nanoparticles into short NiO rods.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…At the initial stage of thermal oxidation under the above conditions, the bulk Ni surface was formed into NiO shells by contacting with oxygen at high temperature and it transformed into a p-type semicon-ductor with Ni 2+ vacancies. 39 As the thermal oxidation further progressed, the NiO NSs were grown mainly by the cationic diffusion (that is, the Ni 2+ ions are diffused outward through NiO shells) and the size of NiO was increased. After that, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The analyses of MayIM at higher magnification ( Fig. 15 ) show darker spherical Ni 0 particles [24] and some plates structure of the matrix ( Fig. 15 a).…”
Section: Tem Analysis: Morphology Changes and Carbon Formationmentioning
confidence: 98%